Pengaruh Citra Merek, Harga, Dan Promosi Terhadap Keputusan Pembelian Produk Minyak Rambut Pangeran Pomade Di Sumenep - Agustin, Rose Dwi; Purnomo, Hadi (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research aims to analyze the influence of brand image on purchasing decisions for Prince Pomade hair oil products in Sumenep. To analyze the influence of price on purchasing decisions for Prince Pomade hair oil products in Sumenep. To analyze the influence of promotions on purchasing decisions for Prince Pomade hair oil products in Sumenep. The data collection technique used in this research is by using a questionnaire. This research uses a quantitative approach with a total of 100 respondents. The analysis technique used is multiple linear regression, classical assumption test, t test, and coefficient of determination. The research results show that partially the Brand Image and Promotion variables have a positive and insignificant effect on purchasing decisions for Prince Pomade hair oil products in Sumenep. Meanwhile, the price variable has a significant positive effect on the decision to purchase Prince Pomade hair oil products in Sumenep